Photopolymerizable platelet lysate hydrogels for customizable 3D cell culture platforms - Santos, Sara C (2019)
3D cell culture platforms have emerged as a setting that resembles in vivo environments replacing the traditional 2D platforms. Over the recent years, an extensive effort has been made on the development of more physiologically relevant 3D cell culture platforms. Extracellular matrix-based materials have been reported as a bioactive and biocompatible support for cell culture. For example, human plasma derivatives have been extensively used in cell culture. Despite all the promising results, in most cases these types of materials have poor mechanical properties and poor stability in vitro. Here plasma-based hydrogels with increased stability are proposed. Platelet lysates are modified by addition of methacryloyl groups (PLMA) that polymerize in controlled geometries upon UV light exposure. The hydrogels could also generate porous scaffolds after lyophilization. The results show that PLMA materials have increased mechanical properties that can be easily adjusted by changing PLMA concentration or modification degree. Cells readily adhere, proliferate, and migrate, exhibiting high viability when encapsulated in PLMA hydrogels. The innovation potential of PLMA materials is based on the fact that it is a complete xeno-free solution for human cell culture, thus an effective alternative to the current gold standards for 3D cell culture based on animal products.